Rolling Motion Control Introducing Back Bending for Acrobot Composed of Rounded Links. Issue 1 (July 2017) - Murakami, Naoto; Sugimori, Atsuto; Ibuki, Tatsuya; Sampei, Mitsuji
Abstract: This paper proposes a rolling motion scheme for Acrobot composed of two links with curved contours. A feature of the present rolling control is to introduce back bending motion with hope for no strong impact on the ground. First, the Acrobot model is classiéd into eight models according to the arcs in contact with the ground since the model differs with contact points on the ground. Rolling control strategy is next proposed by considering no impact conditions, kinetic energy and potential energy. Then, an output function, to be zero, is designed and output zeroing control is applied to achieve the rolling motion. Here, the output function is built by the two link angles and designed to follow a desired path given by a bezier curve. The curve is optimized to minimize the input energy while guaranteeing the achievement of rolling motion. Finally, simulation and an experiment are conducted for verification.